2003
DOI: 10.1111/j.1348-0421.2003.tb03441.x
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and Immunological Analysis of a Novel Variant of Shiga Toxin 1 from Bovine Escherichia coli Strains and Development of Bead‐ELISA to Detect the Variant Toxin

Abstract: A novel variant of Shiga toxin 1 (Stx1) was identified from bovine Escherichia coli strains. The stx1 variant genes designated as stx1v51 and stx1v52 were cloned and sequenced. The two variant genes differed each other by 2 bp, but the deduced amino acid sequences of the two Stx1 variant toxins were the same and had 94% and 92% homology to that of prototype A and B subunits of Stx1, respectively. The variant toxin designated as Stx1v52 was purified to homogeneity. Although inhibition of protein synthesis in vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 41 publications
0
12
0
Order By: Relevance
“…1). Two clusters corresponded to the existing subtype nomenclature for subtypes Stx1c (47,66) and Stx1d (11,44). In addition to variant Stx1c-O174-DG131-3 (47,66), variants from Ount HI-N (2), ONT HI-A (1), and ONT HI-C (1) were identified as belonging to subtype Stx1c.…”
Section: Sequence Analysismentioning
confidence: 85%
See 1 more Smart Citation
“…1). Two clusters corresponded to the existing subtype nomenclature for subtypes Stx1c (47,66) and Stx1d (11,44). In addition to variant Stx1c-O174-DG131-3 (47,66), variants from Ount HI-N (2), ONT HI-A (1), and ONT HI-C (1) were identified as belonging to subtype Stx1c.…”
Section: Sequence Analysismentioning
confidence: 85%
“…In addition to variant Stx1c-O174-DG131-3 (47,66), variants from Ount HI-N (2), ONT HI-A (1), and ONT HI-C (1) were identified as belonging to subtype Stx1c. Only variant Stx1d-ONT-MHI813 (11,44) was found in the subtype Stx1d cluster. Two identical amino acid sequences were found for S. dysenteriae (strain 3818T) and Shigella sonnei (strain CB7888).…”
Section: Sequence Analysismentioning
confidence: 94%
“…Analysis of the sequence data of the stx1d ‐positive strains (IF Ec AB8SF, IF Ec AB8Hp, IF Ec LR2) showed that they are identical (100% nucleotide homology) among each other and show 99% nucleotide homology with stx1d (strain MHI 813; Bürk et al. 2003), stx1v52 and stx1v51 genes (strains 92–1251 and 92–1252; Ohmura‐Hoshino et al. 2003).…”
Section: Resultsmentioning
confidence: 99%
“…Only two variants of Stx1a have been identified: Stx1c and Stx1d. Both Stx1c and Stx1d can be distinguished immunologically from Stx1 (13, 14). Stx1c and Stx1d are rarely found in human disease, and when associated with STEC isolated from patients, are linked with a mild disease course (15, 16).…”
Section: Typing and Nomenclaturementioning
confidence: 99%